Perlindungan Privasi Sebagai Hak Individu dalam Islam dan Implementasi di Dunia Digital - Nurcahyani Nurcahyani (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study examines the protection of privacy as an individual right in Islam and its application in the digital age, using a qualitative method based on a literature review. This study analyses Islamic teachings alongside contemporary digital issues to understand how Islamic values can address privacy challenges in the modern era. The findings indicate that Islam places great emphasis on privacy protection through ethical principles such as the prohibition of spying (tajassus), upholding human dignity, respecting personal boundaries, and promoting ethical communication. In the digital age, these principles remain highly relevant in addressing issues such as the misuse of personal data, cybercrime, online fraud and the unethical dissemination of information. This study also highlights the importance of strengthening digital literacy grounded in Islamic values to encourage responsible, mutually respectful, and ethical behaviour in online interactions. Overall, the study concludes that Islamic teachings provide an important ethical foundation for protecting privacy and helping to create a safer, wiser, and more harmonious digital environment for society.